Antioxidant and hepatoprotective activities of Juniperus excelsa M. Bieb against bile duct ligation-induced cholestasis - Ghaidafeh Akbari; Mohammad Reza Abasi; Maral Gharaghani; Sadegh Nouripoor; Nasrin Shakerinasab; Mahdokht Azizi; Marjan Salahi; Farzaneh Karimi; Mahdieh Eftekhari; Damoun Razmjoue; Amir Hossein Doustimotlagh (Wolters Kluwer Medknow Publications, 2024)
Background and purpose: Cholestasis is caused by a malfunction of the biliary liver system. Oxidative stress plays an essential role in the progression of cholestasis. This study aimed to investigate the antioxidant and hepatoprotective effects of ethanolic extract of Juniperus excelsa M. Bieb (JE) fruits on hepatic impairment induced by bile duct ligation (BDL) in rats. Experimental approach: Forty male Wistar rats were randomly divided into 4 groups; sham control + vehicle (SC), BDL + vehicle (BDL), BDL + JE extract (BDL + JE), and SC + extract (SC + JE). One day after surgery, the animals were treated with vehicle or ethanolic extract of JE (500 mg/kg/day) for 7 days. Finally, the blood was taken for biochemical and oxidative stress analysis. Furthermore, the liver tissue of rats was removed for histological examination. Findings/Results: Treatment with the extract of JE decreased the ALP level, whereas it enhanced total protein content compared to the BDL group. Also, JE increased the activity of SOD and GPx, as well as FRAP content compared to the BDL group; while it did not significantly affect the levels of MDA and inflammation markers. However, JE could not improve BDL-induced histopathological alterations in hepatic tissue. Conclusion and implication: This study demonstrated that JE may be useful as an adjuvant therapy by attenuating ALP activity, increasing serum total protein and FRAP content, as well as improving the antioxidant enzymes activity of SOD and GPx. However, further research is warranted to explore the other underlying mechanisms of action.